Montmorency cherry supplementation enhances 15 km cycling time trial performance: Optimal timing 90‐min pre‐exercise - Wangdi, Jimmy T.; O’Leary, Mary F.; Kelly, Vincent G.; Tang, Jonathan C. Y.; Bowtell, Joanna L. (European journal of sport science, 2024)
Montmorency cherry (MC) can improve endurance performance, but optimal pre‐exercise timing of supplementation and influence of training status on efficacy are unknown. We investigated the effect of MC concentrate ingestion between 30‐ and 150‐min pre‐exercise in trained and recreational cyclists on 15‐km time trial (TT) performance and exercise economy. Twenty participants (10 recreationally active, RA; 10 trained, T) completed 10 min of steady‐state exercise (SSE) at 40%Δ (SSE) and a TT on four separate occasions following an unsupplemented (US), 30‐, 90‐ or 150‐min pre‐exercise Montmorency cherry concentrate (MCC) supplementation conditions (MCC30/90/150min). Venous and capillary blood samples were taken at regular intervals pre‐ and post‐SSE and TT. MCC significantly improved TT performance, but not exercise economy. The greatest improvement in performance occurred following MCC90min compared to US (US 1603.1 ± 248 s vs. MCC90min 1554.8 ± 226.7 s, 2.83% performance improvement). Performance was significantly enhanced for trained (US 1496.6 ± 173.1 s vs. MCC90min 1466.8 ± 157.6 s) but not recreationally active participants. Capillary [lactate] and heart rate were significantly greater during the TT for the 90‐min dose timing (p < 0.05). In the MCC30min and MCC90min conditions, plasma ferulic (US 8.71 ± 3.22 nmol. L−1 vs. MCC30min 15.80 ± 8.69 nmol. L−1, MCC90min 12.65 ± 4.84 nmol. L−1) and vanillic acid (US 25.14 ± 10.91 nmol.L−1 vs. MCC30min 153.07 ± 85.91 nmol. L−1, MCC90min 164.58 ± 59.06 nmol. L−1) were significantly higher pre‐exercise than in US and MCC150min conditions (p < 0.05). There was no significant change in muscle oxygenation status or plasma nitrite/nitrate concentration. MCC supplementation enhanced endurance exercise performance optimally when consumed ∼90 min pre‐exercise producing maximal plasma phenolic metabolites during exercise. The ergogenic effect was greater for trained participants. Highlights Acute single‐dose supplementation of Montmorency cherry concentrate (MCC) (>800 mg polyphenols) improved endurance cycling time trial (TT) performance by 2.83% or 48.3 s. Supplementation 90 min prior to exercise produced the greatest increases in plasma phenolic metabolites and improvement in performance, suggesting the ergogenic effects are mediated by these metabolites. Trained but not recreationally active (RA) participants experienced ergogenic effects from cherry supplementation throughout the TT.